Pengenalan High-Level Inquiry-based Science Laboratory Berorientasi Keterampilan Proses - Risa Dwita Hardianti; Stephani Diah Pamelasari; Muhammad Ahganiya Naufal; Sri Ngabekti (Universitas Negeri Semarang, 2026)
Practical work is an important part of learning science. It is a hands-on activity that helps students to understand concepts by observing the phenomena presented. On average, science teachers in MGMP IPA Kota Semarang conduct practical learning in the laboratory 3-4 times per semester. However, the practical work carried out so far has been limited to cooking book experiments or activities with a low level of inquiry. Consequently, aspects such as planning and conducting investigations, which are key components of science process skills, have not been developed. It is necessary to implement training in high-level inquiry in science practicums (i.e., high-level inquiry-based science laboratory) with an orientation towards science process skills. The purpose of the training is to support the development of science teachers' pedagogical competence in designing junior high school science practicum activities that emphasize process skills. This program was implemented using the Asset-Based Community Development (ABCD) approach at MGMP IPA Kota Semarang. The implementation of a high-level inquiry-based science laboratory (HisLab) to strengthen science teachers' laboratory skills was very well received. Two groups conducted open-inquiry labs, while the other two conducted guided-inquiry labs. Teachers are regarded as successful in applying the two types of inquiry labs categorized as HisLab.